Seroprevalence of Chlamydia abortus in Anestrous Cattle of Nawalpur and Chitwan District, Nepal - Pokharel, S; Sharma, S; Acharya, M.P (Nepalese Veterinary Journal, 2023)
Chlamydia abortus are gram negative coccoid, obligate intracellular zoonotic bacteria responsible for abortion and other reproductive problems in dairy cattle. This leads to sub-fertility and infertility in cattle thereby causing significant economic losses to dairy farmers. However, the status of Chlamydia abortus in Nawalpur and Chitwan districts, which are the dairy pockets of Nepal, are poorly understood. The objective of this study was to determine the seroprevalence of antibodies to Chlamydia abortus in anestrous dairy cattle of Nawalpur and Chitwan districts in relatively low risk winter season. In total, 92 cattle serum (Nawalpur (n= 27) and Chitwan (n= 65) samples were collected from April 2018 to May 2019 and tested using a Chlamydia abortus specific indirect ELISA kit to evaluate the seropositivity status of cattle. Results showed that only 2 (2.17%) cattle were seropositive for Chlamydia abortus. Both the positive cattle were Jerseys from Nawalpur area with a history of abortion. The ages of the seropositive cattle were 3 and 4 years. In conclusion, there was a low seroprevalence of C. abortus in dairy cattle of Nawalpur and Chitwan districts. The presence of this bacterium suggests that it is likely to be a cause of unidentified abortion in dairy cattle in Nepal. We suggest screening dairy animals for C. abortus infection to minimize this risk.